Longitudinal oscillations in system of charged particles with dipole moment - Молдабеков, Ж.А.; Рамазанов, Т.С.; Габдуллин, А.Ж. (Recent Contributions to Physics, 2016)
In this paper, we investigate the effect of an additional weak dipole-dipole interaction on the density oscillations of charged particles system where the interaction potential is screened Yukawa potential. In the studies, we used the method of molecular dynamics.We constructed autocorrelation function of the particle velocities (ACF) to study the dynamic properties of the system. In the same vein we studied the frequency of longitudinal vibrations with the help of Fourier transform of the autocorrelation function of the velocities. It was found that in two-dimensional Yukawa fluid frequency of longitudinal oscillations of the particles becomes sensitive with changing of coupling parameter, if even there is a little additional dipole-dipole interaction between the particles.